J. Plantas de D. Ángel Guirao (¿-1890) en el herbario del Real Colegio Alfonso XII de San Lorenzo de El Escorial (Madrid, España). - Perea, Domingo; Carrasco de Salazar, María Andrea; Rodríguez-calcerrada, J.; Millanes, A.M. (Botanica Complutensis, 2001)
CARRASCO, M.A., MILLANES, A. M., PEREA, D. & RODRÍGUEZ-CALCERRADA, J. 2001. Plants from Ángel Guirao (?-1890) in the herbarium of Real Colegio Alfonso XII of San Lorenzo de El Escorial (Madrid, Spain). Bot. Complutensis 25: 329-338. In this paper we describe eighty seven sheets of vascular plants belong to Guirao herbarium recently found in the Real Colegio Alfonso XII of San Lorenzo del Escorial (Madrid). The importance of this rediscovered sheets is, besides its historical relevance, that they were used as reference to established the corology of the species in the classic Prodromus Florae Hispanicae, by Willkomm and Lange. The remaining sheets are reported at the end of the paper.